Human nicotinic acetylcholine receptor alpha-subunit isoforms: origins and expression. - MacLennan, C (1993)
A majority of the autoantibodies in the disease myasthenia gravis (MG) are directed against the alpha-subunit of the muscle nicotinic acetylcholine receptor (AChR). Unlike AChR alpha-subunits previously characterised from other species, the human alpha-subunit exists as two isoforms. The isoforms are generated by alternate splicing of an additional exon located between exons P3 and P4, termed P3A. The 25 amino acids encoded by the P3A exon are incorporated into the extracellular region of the alpha-subunit, and so may be relevant to the pathogenesis of MG. Genomic sequences from rhesus monkey, and from dog and cat, which are susceptible to MG, were characterised between AChR alpha-subunit exons P3 and P4. Although regions homologous to the P3A exon were identified for each of these species, analysis by RT-PCR showed that they are not expressed. At variance with a previous report, constitutive expression of mRNA encoding the human P3A+ alpha-subunit isoform was not detected in heart, kidney, liver, lung or brain. Differential expression of the two alpha-subunit isoforms was not seen during fetal muscle development or in muscle from MG patients. In all cases where mRNAs encoding the two alpha-subunit isoforms have been detected, they are present at an approximate 1:1 ratio.